Consistency, longitudinal stability, and predictions of elementary school students' task interest, success expectancy, and performance in mathematics. (August 2018) - Nuutila, Katariina; Tuominen, Heta; Tapola, Anna; Vainikainen, Mari-Pauliina; Niemivirta, Markku
Abstract: This study examined cross-task consistency and longitudinal stability in elementary school students' task interest, success expectancy, and performance from fourth to sixth grade, and their predictive effects on sixth-grade intrinsic value, self-concept, and achievement in mathematics. The results demonstrated consistency in interest, success expectancy, and performance across tasks and stability over time, and these to predict domain-specific motivation and achievement. Virtually no evidence for reciprocal effects was found for task-specific measures, as only previous task performance predicted change in later success expectancy. Cross-lagged effects were observed, however, for predictions of task motivation and performance on domain-specific motivation and achievement, so that success expectancy predicted intrinsic value, interest predicted self-concept, and task performance predicted both self-concept and achievement. Based on the findings, it would seem that students' task-related motivational experiences are associated with their domain-specific beliefs, and that those, in turn, are to some extent manifested in students' task motivation. Highlights: Task motivation and its predictions were studied in elementary school over two years. There was consistency in task interest, success expectancy, and performance. These further predicted intrinsic value, self-concept, and achievement in mathematics. Compared to girls, boys reported higher success expectancy and change in it. Task motivation seems to contribute to domain-specific motivation and vice versa.